P109: A retrospective cohort comparing symptom management of breathlessness and pain in cancer versus non-cancer conditions. (May 2019) - Robinson, B.; Carter, A.; Goldstein, J.; Harrison, M.; Arab, M.
Abstract : Introduction : In Nova Scotia, under the Paramedics Providing Palliative Care program, paramedics can now manage symptom crises in patients with palliative care goals and often at home without the need to transport to hospital. Growing recognition that non-cancer conditions benefit from a palliative approach is expanding the program. Our team previously found treatment of pain and breathlessness is not optimized, pain scores are underutilized, and paramedics were more comfortable (pre-launch) with a palliative approach in cancer versus non-cancer conditions. Our objective was to compare symptom management in cancer versus non-cancer subgroup.Methods : We conducted a retrospective cohort study. The Electronic Patient Care Record and Special Patient Program were queried for patients with palliative goals from July 1, 2015 to July 1, 2016. Descriptive analysis was conducted and results were compared with a t-test and Bonferroni correction (alpha = p < 0.007).Results : 1909 unique patients; 765/1909 (40.1%) cancer and 1144/1909 (59.9%) non-cancer. Female sex: cancer 357/765 (46.7%), non-cancer 538/1144 (47.0%). Mean age cancer: 73.3 (11.65), non-cancer 77.7 (12.80). Top non-cancer conditions: COPD (495/1144, 43.3%), CHF (322/1144, 28.1%), stroke (172/1144, 15.0%) and dementia (149/1144, 13.0%). Comorbidities for cancer patients (range): 0 to 3; non-cancer 0 to 5. Most common chief complaint (CC) for cancer and non-cancer: respiratory distress, 10.8% vs 21.5%. Overall, no difference in proportion treated cancer vs non-cancer, 11.5% vs 10.1%, p = 0.35. Some difference in individual therapies: morphine 83/765 (10.8%) vs 55/1144 (4.8%), p < 0.001, hydromorphone 9/765 (1.2%) vs 2/1144 (0.2%), p = 0.014, salbutamol 38/765 (5.0%) vs 5/1144 (0.4%), p < 0.001 and ipratropium 27/765 (3.5%) vs 134/1144 (11.7%), p < 0.001, in addition to any support with home medication which is not queriable. Pre-treatment pain scores were documented more often than post-treatment in both groups (58.7% vs 25.6% (p < 0.001), 57.4% vs 26.9% (p < 0.001)).Conclusion : Non-cancer patients represent an important proportion of palliative care calls for paramedics. Cancer and non-cancer patients had very similar CC and received similar treatment, although low proportions, despite pre-launch findings that non-cancer conditions were likely to be undertreated. Pain scores remain underutilized. Further research into the underlying reason(s) is required to improve the support of non-cancer patients by paramedics.